Pengaruh Kinerja Mesin Diesel Yanmar L-40-E-Dt Terhadap Emisi Gas Buang - Surianto Buyung (Industrial Engineering Study Program, Pattimura University, 2011)
This research studies engine performance influence to exhaust emission of gas as diesel fuel fuel mixture to diesel engine performance. Matters harming in exhaust gas is carbon hydrogen, nitrogen monoxide and monoxide carbon. Assaying is done by using exhaust emission of gas test device at encumbering 750, 1000 and 250 at revolution constant 3000 rpm. From result of assaying shows ever greater of encumbering increasingly boosts up engine energy power hence, the oxygen grade declines. ever greater of usage encumbering of fuel increasingly rising , oxygen grade declines, grade dioxide carbon rising, nitrogen oxide grade also experiences derivation, rising monoxide carbon grade. Transformation of efficiency thermal hardly influences derivation and increase of consisting in chemistry elements in exhaust gas, where oxygen grade, rising carbon dioxide, nitrogen oxide grade downwards. Monoxide carbon yielded by diesel engine Yanmar L-40 exhaust gas equal to 0,1% smaller than 0,3% still in condition permitted, competent to be operated